EFFECT OF DIETARY SUPPLEMENTATION OF ACETONE EXTRACTS OF NIGELLA SATIVA L. SEEDS ON SERUM CHOLESTEROL AND PATHOGENIC INTESTINAL BACTERIAL COUNT IN BROILERS - M. N. Siddiqui; M.T. Islam; M.A. Sayed; M.A. Hossain (Journal of Animal and Plant Sciences, 2015)
This study aimed to investigate effects of varying doses of Nigella sativa seed powder or acetone extracts in diet on feed intake, mortality, serum lipid profiles and population of intestinal microflora of broilers. A total 168, day-old broiler chicks (Cobb 500) were  ad-libitium manually prepared feeds supplemented with 0, 1.5, 2.5, 3.0% seed powder or  0, 0.2, 0.4% acetone extracts of N. sativa seed for 4 weeks. The experiment was conducted in a complete randomized design (CRD) with seven treatments and three replications. N. sativa supplemented feed had no significant effects on feed intake, body weight and mortality rate of broiler. However, supplementation of either 3.0% seed powder or 0.4% extracts of N. sativa seeds significantly (p<0.05) decreased serum cholesterol and triglycerides contents in broiler. Furthermore, both N. sativa seed powder and extract supplemented feed also suppressed harmful bacterial (Escherichia coli) population in the feces. These results suggest that N. sativa seed might have potential as an alternative to hazardous synthetic feed additives (antibiotics) to formulate low cost and environment-friendly diet for the broiler.
Keywords: Broiler; Nigella sativa seeds; Serum cholesterol; Escherichia coli